2016
DOI: 10.1007/978-3-319-39745-0_12
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic Impacts—Fisheries

Abstract: Fishers and scientists have known for over 100 years that the status of fish stocks can be greatly influenced by prevailing climatic conditions. Based on historical sea surface temperature data, the North Sea has been identified as one of 20 'hot spots' of climate change globally and projections for the next 100 years suggest that the region will continue to warm. The consequences of this rapid temperature rise are already being seen in shifts in species distribution and variability in stock recruitment. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 155 publications
1
3
0
Order By: Relevance
“…Similar trade-offs are reported by Asadolahi et al (2018) in Iran, Lake Chilwa basin, in Malawi (Mvula & Haller, 2009;Pullanikkatil et al, 2013), and Lake Chad (Zieba et al, 2017). Lake Malombe fishery, for a very long period, supported the livelihoods of thousands of local populations from different parts of the catchment (Pinnegar et al, 2016). However, the fishery has faced a series of combined threats, including over-exploitation, pollution, and invasive species (Walker, 2012).…”
Section: Trade-offs Between Ecosystem Servicessupporting
confidence: 55%
“…Similar trade-offs are reported by Asadolahi et al (2018) in Iran, Lake Chilwa basin, in Malawi (Mvula & Haller, 2009;Pullanikkatil et al, 2013), and Lake Chad (Zieba et al, 2017). Lake Malombe fishery, for a very long period, supported the livelihoods of thousands of local populations from different parts of the catchment (Pinnegar et al, 2016). However, the fishery has faced a series of combined threats, including over-exploitation, pollution, and invasive species (Walker, 2012).…”
Section: Trade-offs Between Ecosystem Servicessupporting
confidence: 55%
“…Huthnance et al 2016), with many documented impacts on fish species and the fisheries dependent on these (e.g. Simpson et al 2011;Heath et al 2012;Pinnegar et al 2016), to our knowledge, this is the first study to have systematically identified extreme temperature events and how these may have impacts on key fish and shellfish stocks.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding effects on fisheries operations, models generally suggest that climate change could result in a north-eastward shift of storm frequency in the North Atlantic, but no clear trend is found in observations from the North Sea and Baltic Sea, and regional projections of storminess remain highly uncertain for these two regions (Pinnegar et al 2016;EN-Clime 2021). Evaluations of the risks and adaptations to climate change from other regions suggest that increasing storminess is likely to disturb fishing operations and limit the number of active fishing days.…”
Section: Effects Of Climate Change On Fisheriesmentioning
confidence: 99%